The Influence of Sustainability Awareness, Corporate Environmental Commitment, Regulatory Pressure, and Perceived Environmental Responsibility on Industrial Environmental Compliance in Jabodetabek - Adira, Myesha; Widayati, Catur (Dinasti International Journal of Digital Business Management, 2025)
Indonesia faces significant challenges in environmental management, marked by severe air pollution and the low compliance of industries with environmental regulations. The government has established a legal framework through Law No. 32 of 2009 and Government Regulation No. 22 of 2021, which introduced two key instruments: the Environmental Impact Assessment (AMDAL) and the Corporate Performance Rating Program in Environmental Management (PROPER). However, compliance remains low, with thousands of companies in the red category, even though the number of PROPER participants increased from 4,520 companies in 2023–2024 to a target of 5,476 companies in 2025. This study aims to analyze the role of environmental laboratories in supporting regulatory compliance by examining the effects of sustainability awareness, corporate environmental commitment, regulatory pressure, and perceived environmental responsibility on corporate compliance. A quantitative approach was applied using 210 respondents, analyzed through descriptive statistics and SEM-PLS. The results reveal that sustainability awareness, corporate environmental commitment, and regulatory pressure significantly influence compliance, while perceived environmental responsibility acts as a mediating variable. These findings highlight the strategic role of environmental laboratories in providing scientific data for AMDAL and PROPER assessments, strengthening regulatory integration, and encouraging industries to adopt laboratories as strategic partners to improve compliance and promote sustainability